Effect of Collagen Matrix Saturation on the Surface Free Energy of Dentin using Different Agents - de Almeida, Leopoldina de Fátima Dantas [UNESP]; Souza, Samilly Evangelista; Sampaio, Aline Araújo; Cavalcanti, Yuri Wanderley; da Silva, Wander José; Del Bel Cur, Altair A.; Hebling, Josimeri [UNESP] (My University, 2015)
INTRODUCTION: The surface free energy of conditioned-dentin is one of the factors that interfere with monomeric infiltration of the interfibrillar spaces. Saturation of the tooth matrix with different substances may modulate this energy and, consequently, the wettability of the dentin. AIM: To evaluate the influence of different substances used to saturate conditioned-dentin on surface free energy (SFE) of this substrate. MATERIALS AND METHODS: Dentin blocks (4 × 7 × 1 mm, n = 6/ group), obtained from the roots of bovine incisors, were etched using phosphoric acid for 15 seconds, rinsed and gently dried. The surfaces were treated for 60 seconds with: ultra-purified water (H20-control); ethanol (EtOH), acetone (ACT), chlorhexidine (CHX), ethylenediaminetetraacetic acid (EDTA); or sodium hypochlorite (NaOCl). The tooth surfaces were once again dried with absorbent paper and prepared for SFE evaluation using three standards: water, formamide and bromonaphthalene. Analysis of variance (ANOVA) and Dunnet's tests (a = 0.05) were applied to the data. RESULTS: Ethylenediaminetetraacetic acid was the only substance that caused a change to the contact angle for the standards water and formamide, while only EtOH influenced the angles formed between formamide and the dentin surface. None of the substances exerted a significant effect for bromonaphtha-lene. In comparison to the control, only EDTA and NaOCl altered both polar components of the SFE. Total SFE was increased by saturation of the collagen matrix by EDTA and reduced when NaOCl was used. CONCLUSION: Saturation of the collagen matrix by EDTA and EtOH changed the surface free energy of the dentin. In addition, the use of NaOCl negatively interfered with the properties evaluated. CLINICAL SIGNIFICANCE: The increase of surface free energy and wettability of the dentin surface would allow higher penetration of the the adhesive system, which would be of importance to the clinical success of resin-dentin union.
Keywords: Dentin; Surface free energy; Surface properties; Tooth acid-etching